Mechanical properties and fracture behavior of natural fiber-glass fiber reinforced epoxy matrix hybrid composites - Mawarnie, Ismail (2021)
The world today is experiencing a significant global warming problem. One of the reasons for this problem is the use of unlimited synthetic and polymer materials. Many industries have used this natural fiber reinforced polymer composite, including in the furniture, automotive, aerospace, and shipping industries. However, the main weakness of this composite is the lack of mechanical properties, such as strength, compared to synthetic fiber composites applied in many products. Therefore, it is believed that the composite manufacturing method through the hybridization of natural fibers with synthetic fibers compensates for their respective advantages and disadvantages. Natural fibers have excellent mechanical properties but are unable to compete with synthetic fibers. Meanwhile, synthetic fibers are expensive and non-disposable, and have high density. Synthetic fibers are different from natural fibers that have lower density, low cost, and biodegradable. The main aim of this study was to determine the effect of hybridization on the mechanical properties of natural-glass fiber reinforced epoxy matrix hybrid composites. The fractured samples from the tensile test were observed using scanning electron microscopy (SEM) for morphological analysis. This study was chosen due to the fewer findings of this hybrid composite, mainly studies using pineapple leaf fiber (PALF) and rice husk (RH) fiber as natural fibers although these fibers are waste materials with a high content of hemicellulose and cellulose. The fabrication process of this hybrid composite started with the grinding of natural fibers to obtain short fibers, followed by the subsequent separation of fibers, drying, and formation of the hybrid composites. The composition of the fiber and epoxy matrix was based on weight distribution, where 30 wt. % was from the combination of natural and glass fibers, and the remaining 70 wt. % was the epoxy matrix. The fraction of glass fiber ranged from 25 wt. % to 5 wt. %, and vice versa for natural fibers, and the bi-directional type of glass fiber was used in this study. The lamination for all the fibers alternated with the beginning of the glass fiber from the bottom. The epoxy absorption process adopted the hand lay-up method whereas the curing process applied the cold compression method. After conducting a series of tensile, flexural, and impact tests, the results showed that the highest strength of RH and PALF hybrid composite was similar to 30 wt. % of glass fiber with a difference of less than 10%, and achieved even higher modulus than the glass fiber composite solely. Overall, the hybrid composite with weight distribution of 25 wt. % of glass fiber and 5 wt. % of natural fiber, either PALF or RH, showed the highest strength for tension, bending, and impact tests due to the weight of glass fiber and excellent interfacial bonding between fibers and epoxy. The values obtained by the PALF-glass fiber hybrid composite were 223.58 MPa for tensile strength, 290.11 MPa for bending, and 469.52 J/m for impact. The values for RH-glass fiber hybrid composite for tensile test were215MPa, 275.51MPa for flexural and 447 J/m for impact strength. However, the internal structure after fractured showed more voids and fiber pull-out when the natural fiber increased. Therefore, this study shows that the hybrid composites between PALF and RH fibers with glass fibers have great potential to be used in place of existing synthetic fiber composites in the industry.